Suppression of erythropoiesis by dietary nitrate. Issue 3 (24th November 2014) - Ashmore, Tom; Fernandez, Bernadette O.; Evans, Colin E.; Huang, Yun; Branco‐Price, Cristina; Griffin, Julian L.; Johnson, Randall S.; Feelisch, Martin; Murray, Andrew J.
Abstract : In mammals, hypoxia‐triggered erythropoietin release increases red blood cell mass to meet tissue oxygen demands. Using male Wistar rats, we unmask a previously unrecognized regulatory pathway of erythropoiesis involving suppressor control by the NO metabolite and ubiquitous dietary component nitrate. We find that circulating hemoglobin levels are modulated by nitrate at concentrations achievable by dietary intervention under normoxic and hypoxic conditions; a moderate dose of nitrate administered via the drinking water (7 mg NaNO3 /kg body weight/d) lowered hemoglobin concentration and hematocrit after 6 d compared with nonsupplemented/NaCl‐supplemented controls. The underlying mechanism is suppression of hepatic erythropoietin expression associated with the downregulation of tissue hypoxia markers, suggesting increased pO2 . At higher nitrate doses, however, a partial reversal of this effect occurred; this was accompanied by increased renal erythropoietin expression and stabilization of hypoxia‐inducible factors, likely brought about by the relative anemia. Thus, hepatic and renal hypoxia‐sensing pathways act in concert to modulate hemoglobin in response to nitrate, converging at an optimal minimal hemoglobin concentration appropriate to the environmental/physiologic situation. Suppression of hepatic erythropoietin expression by nitrate may thus act to decrease blood viscosity while matching oxygen supply to demand, whereas renal oxygen sensing could act as a brake, averting a potentially detrimental fall in hematocrit.—Ashmore, T., Fernandez, B. O., Evans, C. E., Huang, Y., Branco‐Price, C., Griffin, J. L., Johnson, R. S., Feelisch, M., Murray, A. J., Suppression of erythropoiesis by dietary nitrate. FASEB J. 29, 1102–1112 (2015). www.fasebj.org